Extended Pseudo-Subarachnoid Hemorrhage Post-Percutaneous Coronary Intervention - Benjamin Honton, MD (JACC: Case Reports, 2020)
We report the case of an extended pseudo-subarachnoid hemorrhage (PSAH) related to contrast intracerebral diffusion from blood-brain barrier breakdown on periprocedural percutaneous coronary intervention right corticofrontal ischemic stroke. PSAH is a rare and complex phenomenon, and it is important to differentiate PSAH from subarachnoid hemorrhage to avoid inappropriate treatment with potentially severe consequences. (Level of Difficulty: Beginner.)